Keratin 17 is Not Always a Marker of Proliferation of Keratinocytes in Skin Diseases - Cui L; Zhu Z; Feng Y; Zhang Y (Dove Medical Press, 2021)
Li Cui,1 Zirong Zhu,2 Yiguo Feng,3 Yanfei Zhang3 1Department of Dermatology, Shaanxi Provincial People's Hospital, Xian, People's Republic of China; 2Department of Dermatology, Xi'an People's Hospital, Xian, People's Republic of China; 3Department of Dermatology, The Second Affiliated Hospital of Xi'an Jiaotong University, Xian, People's Republic of ChinaCorrespondence: Yanfei ZhangDepartment of Dermatology, The Second Affiliated Hospital of Xi'an Jiaotong University, Xian, People's Republic of ChinaEmail zhangyanfei723@163.comPurpose: Keratin 17 (K17) is an embryonic keratin and overexpression is seen in psoriasis, which is a hyperproliferation skin disease. Nonetheless, whether it is also highly expressed in other proliferative skin diseases remains unclear. The aim of this study is to explore the expression of K17 in cutaneous lichen planus (CLP), lichen simplex chronicus (LSC), and prurigo nodularis (PN).Methods: A total of 20 skin samples from CLP lesions, 20 from LSC lesions, 20 from PN lesions, and 10 healthy adult skin tissues were obtained. Then, the expression of K17 was analyzed using immunohistochemistry on paraffin-embedded tissue sections. Furthermore, quantitative and semi-quantitative immunohistochemical scores of K17 were independently evaluated under a microscope by 2 dermatologists.Results: Immunohistochemical analysis revealed that in normal skin, K17 was minimally expressed. Nevertheless, it was highly expressed in all epidermal layers in CLP lesions (P-value < 0.01), and negatively expressed in LSC and PN lesions (all P-value > 0.05). The average gray value of K17 in CLP was 151.153± 13.985 (P-value < 0.001), while the average values of K17 in LSC and PN were 178.720± 12.001 and 181.316± 8.920, respectively (all P-value > 0.05).Conclusion: K17 is potentially expressed in certain inflammatory skin diseases, including psoriasis and lichen planus. Besides, it is not always a marker of hyperproliferation of keratinocytes in skin diseases.Keywords: keratin 17, proliferation of keratinocytes, inflammatory skin diseases